2017
DOI: 10.1017/cjn.2017.263
|View full text |Cite
|
Sign up to set email alerts
|

Demographics, Interests, and Quality of Life of Canadian Neurosurgery Residents

Abstract: Despite a challenging residency and high workload, the majority of Canadian neurosurgery residents are happy and satisfied with their choice of specialty and program. However, work-life balance, employability, resident intimidation, and depression were identified as areas of active concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The number of neurosurgical trainees pursuing PhDs is steadily increasing, from 10% to 26% over the past two decades at high ranking academic centers in the United States 11 . A recent Canadian survey similarly found 25% of trainees obtaining PhDs and 33% obtaining a Masters 1,15 . There is no doubt that pursuing a graduate degree confers benefits useful to an academic neurosurgeon in general.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The number of neurosurgical trainees pursuing PhDs is steadily increasing, from 10% to 26% over the past two decades at high ranking academic centers in the United States 11 . A recent Canadian survey similarly found 25% of trainees obtaining PhDs and 33% obtaining a Masters 1,15 . There is no doubt that pursuing a graduate degree confers benefits useful to an academic neurosurgeon in general.…”
Section: Discussionmentioning
confidence: 97%
“…There is no doubt that pursuing a graduate degree confers benefits useful to an academic neurosurgeon in general. In the United States, having a Masters or PhD has been associated with obtaining an academic position and advancement in academic rank 15 . Interestingly, among those with a Masters, only a Masters of Science (and not MBA or MPH) has been associated with hiring to an academic practice in the United States 12 .…”
Section: Discussionmentioning
confidence: 99%
“…ACGME has proposed an 80-h/week duty time limitation. [ 14 15 ] A study done in Canada revealed that 58% residents were satisfied with 80–89 h of duty per week[ 16 ] though this may be exhausting and leaves little time for consolidation of the knowledge and skills. [ 17 ] Sixty-one percent of the private setups have three or more than three OPDs per week, with approximately 150 patients seen in a day.…”
Section: Discussionmentioning
confidence: 99%
“…Neurosurgeons and neurosurgery residents frequently report elevated levels of stress reaching up to 53% in some reports. [ 12 ] A recent US national survey on stress and burnout in the neurosurgical community found that more than one-half of the respondents showed signs of burnout, reporting a higher level of burnout when compared with other medical specialties and that only one-third of respondents would recommend a career in neurosurgery. [ 17 , 20 ] It is likely that during their clinical rotations, medical students sense the stress that neurosurgeons experience during their day-to-day life, which in our study showed to be significantly important factor in deviation away from applying to this specialty.…”
Section: Discussionmentioning
confidence: 99%